Is minimally invasive multi-vessel off-pump coronary surgery as safe and effective as MIDCAB? - Rufa, Magdalena I.; Ursulescu, Adrian; Dippon, Juergen; Aktuerk, Dincer; Nagib, Ragi; Albert, Marc; Franke, Ulrich F. W. (Frontiers in Cardiovascular Medicine, 2024)
The safety and efficacy of minimally invasive direct coronary artery bypass (MIDCAB) surgery has been confirmed in numerous reports. However, minimally invasive multi-vessel off-pump coronary artery bypass grafting (MICS CABG) has lower uptake and has not yet gained widespread adoption. The study aimed to investigate the non-inferiority of MICS CABG to MIDCAB in long-term follow-up for several clinical outcomes, including angina pectoris, major adverse cardiac and cerebrovascular events (MACCE) and overall survival. Methods: This is an observational, retrospective, single center study of 1149 patients who underwent either MIDCAB (n=626) or MICS CABG (n=523) at our institution between 2007 and 2018. The left internal thoracic artery and portions of the radial artery and saphenous vein were used for the patients' single-, double-, or triple-vessel revascularization procedures. We used gradient boosted propensity-score estimation to account for possible interactions between variables. After propensity-score adjustment, the two groups were similar in terms of preoperative demographics and risk profile. Long-term follow-up (mean 5.87, median 5.6 years) was available for 1089 patients (94.8%). Results: A total of 626, 454 and 69 patients underwent single, double and triple coronary revascularization, respectively. The long-term outcomes of freedom from angina pectoris, acute myocardial infarction, and revascularization rate were similar between the two groups. During follow-up, there were 123 deaths in the MIDCAB group and 96 in the MICS CABG group. The 1-, 3-, 5-, and 10-year survival rates were 97%, 92%, 85%, and 69% for the MIDCAB group and 97%, 93%, 89%, and 74% for the MICS CABG group, respectively. The hazard ratio of overall survival for patients with two or more bypass grafts compared to those with one bypass graft was ). This indicates that there was no significant difference in survival between the two groups. Furthermore, if we consider a hazard ratio of 1..2 to be clinically non-relevant, surgery with two or more grafts was significantly non-inferior to surgery with just one graft (p-value = 0.0057). Conclusion: In experienced hands, MICS CABG is a safe and effective procedure. Survival and durability are comparable with MIDCAB.